The Legal Impact of The Covid-19 Pandemic On Efforts To Manage People Smuggling As A Transnational Crime In Indonesia - Joseph Maximillian Eduard Pauner; Natalia Yeti Puspita (Research Collaboration Community (RCC), 2023)
The rapid development of information and transportation technology in the era of globalization has facilitated human mobility to carry out activities and lives. Human mobility can occur between countries, thus creating human migration. The process of human migration between countries requires official documents and must obtain permits. The difficulty of licensing and the absence of complete documents are often the openings for transnational crimes of people smuggling. People Smuggling is also happening in Indonesia. The handling of people smuggling in Indonesia is regulated in Law Number 6 of 2011 concerning Immigration. The COVID-19 pandemic has impacted efforts to deal with people smuggling in Indonesia. Based on this, this study aims to analyze the legal impact of the COVID-19 pandemic on efforts to handle people smuggling as a transnational crime in Indonesia. The research method used is normative juridical. The literature search will be used to obtain secondary data as primary data. Based on the results of the study, it can be seen that the Covid 19 pandemic has caused the Indonesian Government to issue a series of policies. One is the Regulation of the Minister of Health of the Republic of Indonesia Number 9 of 2020 concerning Guidelines for Large-Scale Social Restrictions in the Context of Accelerating the Handling of Corona Virus Disease 2019 (Covid-19). This regulation prevents the mobility of people entering and leaving Indonesia during the pandemic to reduce the transmission of Covid 19. This policy is also one of the strategies to reduce the crime rate of people smuggling.